Pengembangan Admisi Universitas Berbasis Sistem Pengelola Pengetahuan - Nathanael Liman; Maresha Caroline Wijanto; Mewati Ayub; Bernard Renaldy Suteja; Try Atmaja Linggan Jaya (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The study will develop a prototype to implement a knowledge management system using the information retrieval method. As a study case, the knowledge about university admission will be used. The users of the system consist of guests, admin, and admission staff. The guest can search for information in the dashboard and give suggestions. The admission staff can add new knowledge or modify the existing knowledge. The new knowledge should be verified and approved by the admin. The testing was performed to verify that the system works as it should be, especially for information searching. The results show that searchingusing lowercase and without stopword, or punctuation gives better similarity index. Searching using unigram also has better similarity index.